ANALISIS PERMINTAAN CABAI RAWIT MERAH (Capsicum frutescens) DI KABUPATEN SEMARANG - Miftahuddin, Lea; Ekowati, Titik; Setiawan, Bambang Mulyatno (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 1 (2020): Vol. 14 No. 1, 2020, 2020)
Red cayenne papper is a food ingredient that has a high demand at the level of household consumers. Demand for red cayenne is influenced by several factors. Factors demand for red cayenne papper were red cayenne papper prices, curly red chili prices, household consumer income, number of family members and consumer tastes. The research aimed to analyze the determinant factors of red cayenne papper demand and to analyze elasticity of demand of red cayenne pepper in Semarang Regency. The research location determined by purposive. Survey method was used with Quota sampling to select 90 respondents from 3 District in Semarang Regency with the criteria of highest, medium and low red cayenne pepper production. Respondents taken by snowball method. Data were analyzed using multiple linear regression. Regression analyzed showed that independent variabels simultaneosly significant on dependent variabel. Partially the income of consumers, the number of family members and consumer tastes significantly influence the demand for red cayenne pepper. While the price of red cayenne pepper and curly red chili did not significantly affect the demand for red cayenne pepper. Red cayenne pepper elasticity was elastic 0.135 and categorized as normal goods. The income elasticity was 0.317. Curly red chili was substitutes red cayenne pepper with elasticity 0.122.